Dynamics of soil dissolved organic carbon pools reveal both hydrophobic and hydrophilic compounds sustain microbial respiration - Straathof, Angela L.; Chincarini, Riccardo; Comans, Rob N.J.; Hoffland, Ellis (Soil biology & biochemistry, 2014)
The quality of dissolved organic carbon (DOC) released from soil organic amendments may influence soil microbial activity and the quality of the soil's DOC pools. Measurements of total DOC are often considered in relation to microbial activity levels but here we propose that quantification of DOC fractions is a more informative alternative. In a laboratory incubation, soil received DOC that was extracted from three organic matter sources: fresh compost, mature compost, and a mixture of the two. Soil microbial respiration (CO2 emission), and concentrations of hydrophobic (humic acids (HA), fulvic acids (FA) and neutrals (HoN)) and hydrophilic (Hi) DOC fractions were measured throughout the 35 d incubation. The A254 specific UV absorption of total and HA DOC were measured at the start and end of the incubation as an indicator of aromaticity. Microbial respiration rates were highest in soils amended with fresh compost DOC, which had a higher proportion of Hi compounds. Concentration of Hi was significantly and positively correlated with soil respiration, explaining 24% more variation than total DOC. Humic acid concentrations significantly decreased over 35 d, including a 33% reduction in HA from an unamended control soil. Compost treated soils' HA pools increased in aromaticity, suggesting preferential mineralization of the least aromatic HA molecules. A decrease in SUVA254 values in other HA pools may be the result of HA degradation in the absence of low-aromatic HA. Our observation of depletion of hydrophobic compounds from the HA fraction provides evidence that humic substances can be a relatively reactive pool, which can provide, together with hydrophilic compounds, a readily available C source to the microbial community. •We added compost-derived DOC varying in quality to a soil and incubated for 35 d.•The hydrophilic DOC fraction influenced microbial respiration rates the most.•Depletion of humic acids over time corresponded with aromaticity dynamics.•Humic acids, while often assumed to be recalcitrant, are actually biodegradable.